PSVIII-37 Modulation of innate and adaptive immune response genes in bovine neutrophil by Galectin-8. (7th December 2018) - Eluka-Okoludoh, E; Asiamah, E; Ekwemalor, K; Mulakala, B; Adjei-Fremah, S; Worku, M
Abstract: Galectins (Gals) are a family of animal lectins that bind β-galactosides through a carbohydrate recognition domain. Milk somatic cell counts (SCC) are associated with increased migration of neutrophils from blood to milk in response to microbial infection resulting in Mastitis. Gal-8 is a tandem-repeat galectin, secreted intracellularly and extracellularly. It is associated with cow neutrophil migration. Gal-8 has been studied as a possible therapeutic to combat inflammation due to microbial infections. The objective of this study was to evaluate the secretion of Gal-8 and the transcriptional effects of recombinant galectin 8(rGal-8) on cow neutrophils. Blood was collected from (N=10) clinically healthy Holstein-Friesian cows from the North Carolina A&T State University Dairy Unit. Neutrophils were isolated by differential centrifugation of whole blood and treated with rGal-8, (10μg) or maintained in PBS at 37°C for 1 hour, 5% CO2. Total RNA was extracted, reverse transcribed and real-time PCR were carried out using RT 2 Profiler™ Cow Innate & Adaptive Immune Responses PCR Array containing 84 genes, as recommended by the manufacturer (Qiagen). Livak method was used to calculate transcript abundance and fold change (FC>2 considered significant). Plasma was extracted and Gal-8 secretion was determined using cow Gal-8 specific ELISA, and analyzed using PROC ANOVA in SAS version 9.4. The average concertation of Gal-8 was 2.43ng/ml and varied between animals. Exposure to rGal-8 affected the expression of 16 genes, 10 genes were up-regulated, and 6 were down-regulated. The highest up-regulated genes include the Toll-like receptors 9, 1, and 2, chemokine CCR6, adhesion molecule ICAM1, immunosuppressive cytokine IL-10, signaling molecule STAT1. Down-regulated genes include immune pathogenic responses Amyloid Protein Component Serum (APCS), IRF7, NFKB. The functional role of secreted gal-8 and the significance of the identified targets for cow health and homeostasis needs further evaluation.